Isyarat dan Simbol dari Al-Aḥrūf Al-Muqaṭṭa’ah dalam Al-Qur’an - Hamdani Anwar (Refleksi, 2020)
The main focus of this research is the problem related to signs and symbol of al-Aḥrūf al-Muqaṭṭa’ah that are contained in the Qur’an. The questions formulated are 1). How do sufis understand al-Aḥrūf al-Muqaṭṭa’ah and 2). What signs and symbols do they say from the al-Aḥrūf al-Muqaṭṭa’ah. This research is included in the ‘Ulūm al-Qur’ān study. In the term of orientation, this research is included in an effort to explain elements that are still widely debated and not well understood. The data sources used used in this study cinsited of two types, namely primary data sources and secondary data sources. Those included in the primary data sources are the work of the exegesis of Ḥaqāiq al-Tafsīr written by al-Sulāmī, Laṭāif al-Ishārat written by al-Qushayrī and Tafsīr al-Jaylānī written by Abdul Qadir al-Jaylānī. Meanwhile, included in the scondary data sources are some literture that is directly or not realted to this fresearch. The method used in this data collection is literatur data documentation. There are twoconclusion obtained from this study. First, the sufis prefer the inner meaning of the beginning of each surah which consits of Hijaiyah letters, because the outer meaning is difficult or incomprehensible. Second, the sufis differ when they reveal the signs and symbols from the beginning of the surah. There are those who understand it as a sign of Allah and His attributes, and others consider that the beginning of the surah is a sign of the glory of the Prophet Muhammad peace be upon him, especially those related to the person and duty as the messenger of Allah.